Chen’s peiyuan tang and premature ovarian failure: unveiling the mechanisms through network pharmacology - Yang, Xiao; Mao, Yi-Ming; Yao, Chong; Song, Ding-ming; He, Yi-bo; Shen, Wei (Frontiers in Pharmacology, 2024)
Background Chen’s Peiyuan Tang (CSPYT) is a compound herbal formula that has shown the potential to enhance ovarian function and reduce autophagy in ovarian granulosa cells, which plays a crucial role in follicular development and maturation. The application of Chinese herbal medicine offers a promising alternative to traditional hormone replacement therapy (HRT). Methods This study explores CSPYT’s therapeutic mechanisms in treating POF, focusing on its modulation of autophagy through network pharmacology and transcriptomics-based analysis, predicting potential interactions and pathways. KGN cell line and rat ovarian granulosa cells were used for in vitro experiment. 4-Hydroperoxy cyclophosphamide(4-HC) stimulation was carried out for establishing the POF cell model. Q-PCR, Western Blot, Transmission electron microscopy to detect the results. Results According to the drug and disease database, the common targets of Chen’s Peiyuan Tang and premature ovarian failure were screened, combined with autophagy gene targets and transcriptome analysis, and finally 8 intersection targets were obtained, namely CDKN1B, MAPK3, PRKCD, CDKN1A, MAPK1, RAF1, BIRC5, CTSB. Enrichment analysis of 8 genes found that they were closely related to the animal autophagy pathway. Construct PPI network diagram. CytoScape 3.9.1 builds CSPYT Drug Target-POF Disease Target-Autophagy Gene Network Diagram. Based on the PPI network diagram and CytoScape 3.9.1 analysis results, it is estimated that MAPK1 and MAPK3 are the key targets of CSPYT in the treatment of POF. The eight final intersection targets were docked with the corresponding active pharmaceutical ingredients. The one that docked most closely with the MAPK family was naringenin. In cell experiment verification, it was confirmed that Chen’s Peiyuan Tang can inhibit the MAPK signaling pathway, significantly reduce the number of autophagosomes, and reduce autophagy damage in ovarian granulosa cells. Discussion CSPYT can inhibit the MAPK signaling pathway, prevent autophagy overexpression and restore ovarian granulosa cell function, effectively alleviating the disease pressure of POF.